2017
DOI: 10.1007/s13365-017-0550-z
|View full text |Cite
|
Sign up to set email alerts
|

Lyssavirus phosphoproteins increase mitochondrial complex I activity and levels of reactive oxygen species

Abstract: We have previously demonstrated that serine residues at positions 162 and 166 of the rabies virus (RABV) phosphoprotein (P) are critical for oxidative stress induced by CVS in cultured cells. We have now evaluated the P of two street RABV variants and Mokola (MOK) virus. The P of these viruses, like CVS, induces an increase in complex I activities and reactive oxygen species levels in transfected cells. Although the sequence homology of P is only 45% with MOK (higher for street viruses) and CVS, serine residue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…For example, M protein’s apparent modulation of the DDR in the absence of DNA damage might produce a protective environment against virus-induced DNA damage. Indeed, previous studies have indicated that NiV and other mononegaviruses, such as rabies virus, can induce reactive oxygen species (ROS), which can cause DNA damage 39 , 40 . Intriguingly, sequencing of bat genomes, including Pteropodid bats (the natural reservoir of HeV, NiV, lyssaviruses and many other highly pathogenic viruses) revealed that many DNA-damage checkpoint genes have been positively selected for 41 , perhaps to protect bat cells against damage by the large amounts of ROS generated during flight.…”
Section: Discussionmentioning
confidence: 99%
“…For example, M protein’s apparent modulation of the DDR in the absence of DNA damage might produce a protective environment against virus-induced DNA damage. Indeed, previous studies have indicated that NiV and other mononegaviruses, such as rabies virus, can induce reactive oxygen species (ROS), which can cause DNA damage 39 , 40 . Intriguingly, sequencing of bat genomes, including Pteropodid bats (the natural reservoir of HeV, NiV, lyssaviruses and many other highly pathogenic viruses) revealed that many DNA-damage checkpoint genes have been positively selected for 41 , perhaps to protect bat cells against damage by the large amounts of ROS generated during flight.…”
Section: Discussionmentioning
confidence: 99%
“…GPR17 is activated by RABV infection and mediates apoptosis through BAK pathway to inhibit viral replication In addition, some researchers found that RABV N, P, and G proteins were present in mitochondria using proteomics analysis. Kammouni et al 134,135 found that P protein of RABV street strain and Mokola strain could enhance the activity of mitochondrial complex I and increase the level of ROS. The amino acids 139-172 of P protein could interact with mitochondrial respiratory chain complex I (MRCC-I), and S162 and S166 are the critical sites in P protein for this interaction.…”
Section: Mitochondrial Dys Fun C Tion In the Pro Ce Ss Of R Abv Repli...mentioning
confidence: 99%
“…For example, mitochondrial redox state and electron transport activity can be restored by reducing HCV replication in full genomic HCV replicon cells [14]. The phosphoproteins of lyssaviruses, such as rabies virus (RABV) and Mokola (MOK) virus, interact with mitochondrial respiratory chain complex I to cause mitochondrial dysfunction and increase the generation of ROS and oxidative stress [15]. Ebermann et al demonstrated that increasing the activity of mitochondrial respiratory chain complexes I and III inhibited coxsackievirus B3 (CVB3) replication [16].…”
Section: Introductionmentioning
confidence: 99%